Identification of Serum Biomarkers for Intestinal Integrity in a Broiler Chicken Malabsorption Model - Baxter, Mikayla F. A.; Latorre, Juan D.; Dridi, Sami; Merino-Guzman, Ruben; Hernandez-Velasco, Xochitl; Hargis, Billy M.; Tellez-Isaias, Guillermo (Frontiers in Veterinary Science, 2019)
Intestinal health is essential for feed efficiency and growth in animal agriculture and is dependent on barrier function, inflammation and dysbiosis. Our laboratory has published a nutritional model to induce gut inflammation using rye as a source of energy in poultry. More recently, we have used this model as an assessment of a nutritional rehabilitation model for better understanding of childhood undernutrition. The objective of this brief research report was to use a well establish malabsorption model in broiler chickens using corn and rye as an energy source to identify several intestinal health biomarkers in the serum. To screen for inflammatory biomarkers, seven commercially available tests were used including Griess, superoxide dismutase, thiobarbituric acid reactive substances, Total antioxidant capacity, extracellular-signal-regulated kinase, Citrulline, and Interferon-ɣ; total IgA from cloacal swab was also measured. In the present study, chickens fed rye had a significant (P<0.05) reduction in body weight and body weight gain at ten day when compared with chickens that received the corn diet. In the second phase of the experiment, chickens that remain with the corn diet had significant differences in body weight and body weight gain. No significant differences were observed for any of the four antioxidant biomarkers evaluated in the sera (P > 0.05). However, significant differences were observed in serum citrulline and IFN-ɣ, as well as in cloacal IgA, in broiler chickens fed with rye, suggesting their potential use as biomarkers to study intestinal inflammation.